The Importance of Education about Batik: Addressing Misconceptions about the Term Term "Ecoprint Batik" in Schools - Saputri, Supeni (Corak, 2025)
Batik cultural heritage has an important role in education to instill cultural values and national identity in the younger generation. The aim of this research is to analyze misconceptions in the use of the term “batik ecoprint” and how  to respond to them. This research uses descriptive qualitative methods. Data collection techniques include literature studies and interviews with batik experts, teachers, students and ecoprint craftmen. The data analysis technique uses Miles and Huberman analysis techniques which include data reduction, data presentation, and drawing conclusions. The results of this research show the difference between batik and ecoprint techniques which lies in the making process. In short, batik is made by going through a process of waxing, dyeing, and removing wax. Meanwhile, ecoprint is made by direct contact printing of leaves on fabric. So the resulting motif is in the form of a print. The long-term impact of less precise use of the term  batik can obscure understanding of the concept of batik and the authenticity of batik itself. Schools should be a place to spread the correct terms so that there are no misconceptions among the nation’s future generations.ABSTRAKWarisan budaya batik memiliki peran penting dalam pendidikan guna menanamkan nilai-nilai budaya dan identitas nasional pada generasi muda. Tujuan penelitian ini adalah untuk menganalisis miskonsepsi penggunaan istilah “batik ecoprint” serta bagaimana dalam menyikapinya. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik pengumpulan data yaitu dengan studi pustaka dan wawancara terhadap ahli batik, guru, siswa, dan perajin ecoprint. Teknik analisis data menggunakan teknik analisis Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini menunjukkan perbedaan teknik batik dan ecoprint yang terletak pada teknik pembuatannya. Secara singkat, batik dibuat dengan melalui proses pelilinan, pewarnaan, dan pelepasan lilin, sedangkan ecoprint dibuat dengan cara cetak kontak langsung dedaunan pada kain, sehingga motif yang dihasilkan berupa cetakan. Dampak jangka panjang dari kurang tepatnya penggunaan istilah batik dapat mengaburkan pemahaman tentang konsep batik dan keaslian batik itu sendiri. Seharusnya sekolah menjadi tempat untuk menyebarkan bagaimana istilah yang benar agar tidak terjadi miskonsepsi pada generasi penerus bangsa.